Night deliveries and carrier-led consolidation strategies to improve urban goods distribution - Estrada, Miquel; Campos-Cacheda, José-Magín; Robusté, Francesc (Transport, 2018)
Night distribution and consolidation strategies have been proposed in many cities to increase the efficiency of the urban goods distribution system and to reduce the external effects that it causes in terms of emissions. However, the deployment of these initiatives presents a new reallocation of costs and incomes among collaborative stakeholders that take part in. In this paper, an analytical model to estimate the new economic effects caused by these strategies on the involved agents is presented, based on continuous approximations. This model allows decision makers to estimate the transportation cost and emissions savings that will be obtained by each strategy as well as the range of retailer demand in which these strategies are not economically feasible. The results show that night distribution generally outperforms the carrier cost reduction and emissions savings, especially when large vehicles are used in night periods.